Peran UMKM terhadap Stabilitas Ekonomi Indonesia - Afrini Fauziah; Amanda Viola; Andita Rheinisa Ardianti; Friska Maulida; Eustasya Griselda Daeli (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research analyzes the important role of Micro, Small and Medium Enterprises (MSMEs) in maintaining Indonesia's economic stability. MSMEs make a significant contribution to Gross Domestic Income (GDP) and employment, with a contribution of around 61% to GDP and 97% to total employment. In addition, digitalization in the MSME sector has proven to be an important strategy in maintaining competitiveness and business sustainability amidst global economic changes. Through a descriptive qualitative approach, this research highlights the importance of improving the quality of human resources in strengthening the competitiveness of MSMEs. The research results show that strengthening MSMEs contributes to economic growth and reduces social inequality and poverty.